Die ländliche Kulturlandschaft der Hebriden und der Westschottischen Hochlande - Uhlig, Harald (ERDKUNDE, 1959)
The author, who for some years has carried out comparative cultural geographical investigations of the regions of Celtic retreat in the British Isles and Brittany, presents here results of his investigations in northwestern Scotland in whose out-of-the-way location many past forms still exert their influence on the present landscape. In the first section the difficulties of relief and climate, of mossy or rocky soils, and the influences of climate and man on the restricted arable land are described. The extremes of the local climate on the one hand prohibited permanent cultivation on the machair soils, and resulted in dessicatiion and formation of sand dunes, whereas on the other hand on damp sites such as the Isle of Jura reed and sphagnum growth could still be observed on land which had been under the plough for about ten years. Inimical nature is however not the only reason for the difficult situation. The existing contrast between extensive empty spaces and some over-populated coastal stretches, characterized by part-time farming of small holdings, otherwise rare in Great Britain, can only be understood in the light of past social development. The Clan system forms the basis of the development of the cultural landscape. Its settlement unit was the farm of the joint tenants, a social group with pronounced team work, the after effects of which are still felt today. Although there was no custom of divided inheritance, the farmland nevertheless became greatly split up as a result of letting to relations and labourers. Arable shares of 1—2 acres per family resulted and the uneconomic size of these holdings became the main argument of the 18th century reformers. The permanent arable was divided into open strips which changed hands in a periodic rotation, the run-rig system. The farm was the unit of management, but it was a hamlet, not a single farmstead; this is important with reference to the question of the Celtic Einzelhof theory as put forward by A. Meitzen. The farm had its own open infield. The common pasture was usually shared with a number of other hamlets of a township. In the Outer Hebrides there was in addition the outfield on the machair, also worked in run-rig, which belonged to a number of hamlets, and in a few instances this is still so today. This Link between a number of hamlets is probably rooted in common kinship and is similary found in other Celtic areas, and also in Teutonic areas with emphasis on animal husbandry. Similar parallels exist for the settlement; the old clachan hamlet is a parallel to the north-west German drubbel and the open infield to the esch with its langstreifen flur or the Breton m£jou. Prior to the introduction of the potato tillage was largely limited to oats. The infield received all available manure, dung, sea weed, and rotted thatch — a parallel to the north-west German plaggen dungung (manuring with turf) — while the outfield was utilised by an unregulated kind of ley farming. The common pasture grounds were supplemented by summer pastures with flock migration to distant pastures of a similar low altitude, a parallel to the Swedish faboda type of almwirtschaft (or transhumance). The second section describes the changes in the cultural landscape during the 18th and 19th centuries with the clearances, the agglomeration of a great number of people in the coastal regions and their resettlement on crofts running parallel with the formation of large farms. The non-agricultural supplementary occupations like fishing, kelp making, tweed weaving, etc., became from the very start a necessary attribute of the crofter as they are still today. The status in the agrarian society of the crofter and also the cottar and squatter is discussed. The parallelisation of the crofter with the heuerling in Westphalia is not accepted and his characterization in some recent German publication where he was likened to the former type of agricultural labourer in the (German) lowlands is criticized. Neither is it correct to call the joint-tenants of the time before the great changes of the 18th century crofters, as is frequently done. Today the following types of settlement are found: 1st — Remains of the cladians, less compact as a result of depopulation, with traces of the old run-rig infield or with run-rig outfield in the machair; 2nd — Resiting of the dwelling houses in the form of a row by retention of the open fieldstrips; 3rd — Separation or re-allocation in compact crofts of irregular shapes and irregularly distributed; 4th — Settlement in the form of a row with compact strip-shaped crofts, similar to the German (wald-) hufendorfer, but different by their common land and small size of holdings; 5th — Isolated crofts; these are rarely original, they are frequently squatter settlements on the smallest pieces of usable land but most of them are the remains of former hamlets. The complement to these settlement types mentioned was the formation of the large isolated farms and the settling of former joint tenants by the landlords of the 18th century in small ports of urban character (with attempts at industrialization) which now form the service centres and places of tourist trade. With the exception of the overpopulated coastal strips the country suffered depopulation from the middle of the 19th century onward, i.e. after the clearances proper, a parallel to the höhenflucht (population recession of the higher altitudes) in the Alps. The last section deals further with the present agriculture of the crofters and their supplementary occupations. While the latter are on the whole closely tied to the croft, like tweed weaving, or necessitate long periods of absence of members of the family, around Stornoway the crofter is gradually turning into an industrial commuter. The last remains of an almwirtschaft in the British Isles is described on the Isle of Lewis. It is similar to the Alpine and Scandinavian, but is today mostly restricted to young cattle. There is further, as a parallelism to the Mediterranean transhumance (German geographers separate this from almwirtschaft as two different types) the sending of flocks of sheep during the winter to other farms in sheltered sites. Finally the house types are described. The development from the earlier corbelled structures to the black house, of which five regional sub-types were recognised, and its present supersedence by the white house. A later paper is to deal with more detailed examples of types of settlement and economy.